2013
DOI: 10.4103/0972-0707.120932
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcome of revascularization in bilateral, non-vital, immature maxillary anterior teeth supplemented with or without platelet rich plasma: A case series

Abstract: Loss of pulp vitality in an immature permanent tooth arrests root development. This leads to tooth with open apex and weak lateral dentinal walls. Management of such necrotic teeth with immature roots poses several treatment challenges. The documented study was performed to evaluate and compare apexogenesis induced by revascularization, with and without platelet rich plasma (PRP) in non-vital, immature anterior teeth. Three patients having bilateral, non-vital, immature maxillary central incisors with apical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…The efficacy of BCR, or PRP or PRF has proved controversial for the regeneration of teeth: A randomized clinical trial which compared PRP, RPF and BCR concluded that BCR was the standard procedure for revascularization of non-vital permanent immature teeth (Shivashankar et al, 2017 ). Meanwhile another clinical case series of BCR and PRP, concluded that PRP was the most successful therapy (Jadhav et al, 2013 ). Another clinical study, concluded that the regenerative effects of PRP and BCR were similar, except that PRP could increase the root length of immature teeth (Alagl et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of BCR, or PRP or PRF has proved controversial for the regeneration of teeth: A randomized clinical trial which compared PRP, RPF and BCR concluded that BCR was the standard procedure for revascularization of non-vital permanent immature teeth (Shivashankar et al, 2017 ). Meanwhile another clinical case series of BCR and PRP, concluded that PRP was the most successful therapy (Jadhav et al, 2013 ). Another clinical study, concluded that the regenerative effects of PRP and BCR were similar, except that PRP could increase the root length of immature teeth (Alagl et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The successful outcome of the REP can be measured as; the ability to accomplish apical closure of the tooth root, a periapical lesion healing response, root lengthening, and dentinal wall thickening, because these indicate the regeneration of tissues (Jadhav et al, 2013 ; Alagl et al, 2017 ; Shivashankar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complete debridement, thorough disinfection and optimal sealing of the root canal system are the major challenges associated with endodontic treatment of teeth with open apices. [8] The major consideration given in restoring immature, non-vital teeth is to assess the stage of root development and remaining root wall thickness. The traditional apexification technique utilizes long-term intracanal calcium hydroxide to promote the formation of a calcified barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Torabinejad and Faras reported that regenaration of pulp-like tissue in a tooth root canal with the use of PRP in regenerative endodontic treatments 31. Jadhav et al reported three cases that were followed-up clinically and radiographically at 6 and 12 months 32. According to the results of their study, there was a marked difference in periapical healing, apical closure and dentinal wall thickening of teeth treated by revascularization with PRP.…”
Section: Discussionmentioning
confidence: 99%